Studi Eksplanatori dan Konfirmatori Gembala Yang Berprofesi Ganda Berdasarkan Matius 6:24 di Kalangan Pelayan Tuhan Gereja Pentakosta Daerah Jakarta - Yeremia; Suhadi; Wendy Christian Setiawan (VISA: Journal of Vision and Ideas, 2024)
This study aims to examine the tendency of bi-vocational pastors' implementation based on Matthew 6:24 among the ministers of the Jakarta Pentecostal Church; examine what dimensions are most dominant in bi-vocational pastors based on Matthew 6:24 among the ministers of the Jakarta Pentecostal Church; and discover what backgrounds are most dominant in dual-profession pastors based on Matthew 6:24 among the ministers of the Jakarta Pentecostal Church. The research methodology used is quantitative method with data collection through a survey of 126 ministers of the Pentecostal Church of God in the Jakarta area. The approach used is the explanatory-confirmatory approach, which explains the relationship between the variables studied and tests them, then examines and identifies several variables to confirm existing findings through hypothesis testing. There are three hypotheses proposed in this study, namely: First, it is suspected that the tendency of the imlementation of bi-vocational pastors based on Matthew 6:24 among the ministers of the Jakarta Pentecostal Church is in the moderate category. Second, it is suspected that the dominant dimension of bi-vocational pastors based on Matthew 6:24 among the ministers of the Jakarta Regional Pentecostal Church is love. Third, it is suspected that the dominant background of bi-vocational pastors based on Matthew 6:24 among Pentecostal Church of God ministers in the Jakarta area is the last education. From the results of the research analysis through statistical tests using the SPSS application, it was found that the tendency of the implementation of bi-vocational pastors based on Matthew 6:24 among the ministers of the Pentecostal Church in the Jakarta area is moderate, thus the first hypothesis is proven; the dominant dimension in the implementation of bi-vocational pastors is devotion to the master, thus the second hypothesis is not proven; and the dominant background in the implementation of exemplary ministers is the length of service, thus the third hypothesis is not proven. Based on the research findings, the implications of this study are: the tendency of the implementation of Bi-vocational pastors based on Matthew 6:24 among the ministers of the Jakarta Pentecostal Church can still increase through programmes and the length of time pastors and ministers serve. Because the dominant background in the implementation of bi-vocational pastors based on Matthew 6:24 is the length of time pastors and ministers have served.